A recombinant human hyaluronidase sustained release gel for the treatment of post‐surgical edema. (29th October 2013) - Nekoroski, Tara; Paladini, Rudolph D.; Sauder, Daniel N.; Frost, Gregory I.; Keller, Gilbert‐A.
Abstract Background Edema commonly accompanies surgical procedures and when excessive, can adversely affect surgical outcomes. The skin extracellular matrix, including one of its primary components, hyaluronan (HA), is a significant barrier to effective drainage of accumulated edematous fluid. Recombinant human hyaluronidase (rHuPH20) is a human hyaluronidase that acts transiently and locally to depolymerize HA. A non‐liposomal gel formulation that provides a sustained release of rHuPH20 was tested in vivo in a preclinical murine model of acquired lymphedema. Methods Lymphedemic mice were injected 24 hours before surgery, and at 2 and 12 days following surgery with rHuPH20 sustained release gel (PH20 SR gel). Quantitative assessment of treatment response indicated that a single dose of PH20 SR gel resulted in accelerated resolution and reduced severity of post‐surgical edema as compared to the gel vehicle (control). Results Statistically significant enzymatic degradation of HA was demonstrated up to 5 mm from the injection site, and histological analysis confirmed removal of HA up to 72 hours following PH20 SR gel administration. Conclusions These results demonstrate sustained hyaluronidase enzymatic activity that promotes diffusion of accumulated post‐surgical edematous fluid, suggesting that PH20 SR gel may be a useful adjuvant in promoting postoperative edema resolution.